2010
DOI: 10.15760/comminfolit.2010.3.2.80
|View full text |Cite
|
Sign up to set email alerts
|

Using Assessment Data to Inform Library Instruction for First Year Students

Abstract: Seeking ways to develop information literacy skills among first year college students, librarians at our institution developed a pilot program to measure the effects of a multiple library instruction session module on students' research skills in the first semester. The pilot program incorporates a substantial assessment model consisting of a pretest, posttest, and a citation analysis of final papers. Results demonstrate that students who had multiple library instruction sessions during the first semester repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
(8 reference statements)
1
14
0
Order By: Relevance
“…21 Julie Gilbert, through pretests, posttests, and citation analysis, found that first-year students with multiple IL sessions report greater self-efficacy with and more use of library resources. 22 Molly Flaspohler compared a more traditional IL instruction program to a pilot group receiving enhanced IL learning opportunities at a small liberal arts college and found that the more integrated approach produced better student learning. 23 Michael Hearn, also at a small school, discussed an embedded librarian model with an introductory English class and found that the quality of student research improved.…”
mentioning
confidence: 99%
“…21 Julie Gilbert, through pretests, posttests, and citation analysis, found that first-year students with multiple IL sessions report greater self-efficacy with and more use of library resources. 22 Molly Flaspohler compared a more traditional IL instruction program to a pilot group receiving enhanced IL learning opportunities at a small liberal arts college and found that the more integrated approach produced better student learning. 23 Michael Hearn, also at a small school, discussed an embedded librarian model with an introductory English class and found that the quality of student research improved.…”
mentioning
confidence: 99%
“…The librarian felt that more time for guided practice in the initial sessions and more reinforcement on return visits would have been beneficial. Gilbert (2009) stresses the advantages of repeated library instruction, although Beile (2003) reports that while education students' performance on library skills tests improved after a library instruction session, there was no significant effect of repeat sessions. In this project, the lower reference scores in spring 2016, particularly in sections A and B which had abbreviated library sessions, suggested that students benefited from the feedback and reinforcement provided by the librarian in earlier semesters where the lab periods were longer.…”
Section: Discussionmentioning
confidence: 99%
“…18 Many authors have examined the efficacy of IL instruction within first-year seminar programs, while increased collaboration between librarians and subject faculty has been shown to have significant impact on the quality and breadth of IL instruction. 19 Of particular relevance to the current project is Ghandi's 2005 study in which a fivesession, highly collaborative IL instruction model was compared to a one-shot IL instruction model in the same course; the former group of students showed marked improvement in IL concept understanding relative to the one-shot group, as well as greater motivation and satisfaction with the IL course component. 20 Significantly, in the five-session model the librarian was granted access to the course syllabus and tailored their instructional delivery to assignment needs, while both faculty and librarian emphasized IL within content delivery.…”
Section: Literature Reviewmentioning
confidence: 99%